The Development of The Financial Market and its role in attracting FDI - معروف زينة; عصام اسماعيل (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to identify the development of the money market and measure its role in attracting foreign direct investment, through an applied study on a sample from some of Arabic countries: Syria, Lebanon, Jordan, Iraq, and the dependent variable was determined by foreign investment, measured by net incoming cash flows, and the independent variable was market development. The financial index was measured using three indicators: market index, market liquidity, and market contribution. The descriptive analysis method was adopted using cross-sectional data during the period 1990-2020, and the data on the study variables were analyzed using the Eviews 10 program. The search yielded results: - The absence of the effect of the financial market index on net foreign direct investment flows in the countries of the sample studied in the long and short terms. - The absence of the impact of the financial market’s contribution to the net foreign direct investment flows in the countries of the sample studied in the long and short terms. - There is a positive effect of financial market liquidity on net foreign direct investment flows in the sample countries studied in the short term. The research recommended the need to provide economic stability and develop the financial sector, which contributes to the transmission of positive effects of the financial market on foreign investment, as it becomes more secure and attractive to them.